2009
DOI: 10.1111/j.1365-2109.2008.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of using the probiotic Efinol®L during transportation of cardinal tetra,Paracheirodon axelrodi(Schultz), in the Amazon

Abstract: The objective of this experiment was to test the probiotic E¢nol s L during transportation of cardinal tetra, Paracheirodon axelrodi (Schultz). For the transportation, ¢sh were distributed in 18 plastic tanks, of which nine contained the E¢nol s L (10 mg L À 1 ; probiotic treatment) and the remaining had no probiotic (control treatment). Transport lasted 24 h and three di¡erent boxes of each treatment were sampled at 3, 12 and 24 h. Up to the 12-h sampling period, no sig-ni¢cant di¡erence in the survival was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 26 publications
(33 reference statements)
5
42
0
2
Order By: Relevance
“…The concentrations of beta 1,3 glucan tested, which ranged from 10.11 to 19.64 ηg.g wet tissue -1 at the beginning of the transport to 6.63 to 13.91 ηg.g wet tissue -1 on arrival did not differ significantly from those found 24 hours after transport (8.22 to 9.63 ηg.g wet tissue -1 ). Cortisol levels in this study are similar to basal values reported by Gomes et al (2008Gomes et al ( , 2009 ), suggesting this species may respond more moderately to stress caused by this procedure.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The concentrations of beta 1,3 glucan tested, which ranged from 10.11 to 19.64 ηg.g wet tissue -1 at the beginning of the transport to 6.63 to 13.91 ηg.g wet tissue -1 on arrival did not differ significantly from those found 24 hours after transport (8.22 to 9.63 ηg.g wet tissue -1 ). Cortisol levels in this study are similar to basal values reported by Gomes et al (2008Gomes et al ( , 2009 ), suggesting this species may respond more moderately to stress caused by this procedure.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the importance of the ornamental fish trade in the Amazon region, studies that address the impacts of stress arising from the capture and transport process in Amazonian species is still very limited (Gomes et al, 2008(Gomes et al, , 2009Brinn et al, 2012). in the water helps raise conductivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a characterization of the conditions of artisanal fish capturing and shipment of the ornamental fish of the family Loricariidae in the state of Meta, Colombia, Ramírez-Duarte et al (2009) In order to minimize the adverse effects associated with fish shipment, a variety of techniques have been developed to be applied during their shipment, such as reducing the water temperature (Lim et al, 2003;Golombieski et al, 2003), use of anesthetics (Iversen et al, 2009;Hasan & Bart, 2007), zeolite, buffer substances (Singh et al, 2004), probiotics (Gomes et al, 2009), and salt (Carneiro & Urbinati, 2001), among others.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques have been developed to mitigate the negative effects of these procedures. To improve the transport conditions of live fish, and increase their survival rate, various practices have been implemented, such as feeding management (Pan et al, 2010), use of loading densities appropriate to the species (Gomes et al, 2003a(Gomes et al, , 2003bUrbinatiet al, 2004), reduction of water temperature (Golombieski et al, 2003;Lim et al, 2003), and addition of salt (Carneiro and Urbinati, 2001;Gomes et al, 2003a), anesthetics (Iversenet al, 2009;Pramodet al, 2010), and ion exchange resins to the water (Singh et al, 2004), and also the use of probiotics (Gomes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%